The Implementation of the DIANA Method to Map the Spread of Tuberculosis in North Sumatra Visualized on a Website : Mapping Tuberculosis Cases Using DIANA Clustering and Interactive Visualizations - Gunawan, Rizky; Molliq Rangkuti, Yulita; Muslim Karo Karo, Ichwanul (Jurusan Matematika FMIPA UNM, 2025)
Tuberculosis disease has a high prevalence rate in North Sumatra, thus requiring an0 appropriate handling strategy. This article aims to map Tuberculosis cases in North Sumatra Province using the Divisive Analysis (DIANA) method visualized on a website. The DIANA method is used to cluster Tuberculosis case data based on certain characteristic patterns such as case rate, mortality rate, and cure rate. The DIANA (Divisive Analysis Clustering) clustering method starts with the entire data as one large cluster, which is then broken down gradually into smaller subclusters based on the level of dissimilarity between elements. Splitting starts from the element furthest from the cluster center, followed by evaluation of other elements to determine the corresponding cluster. This process continues until clusters are formed at the desired level of granularity. The results of the analysis show that clustering with the DIANA method produces clusters that separate areas with high, medium, and low case rates. Evaluation of clustering using the Davies Bouldin Index (DBI) showed the best value of 0.2943 in 2022. In addition, this article produces a Leafletjs-based interactive map to visualize the clustering results, so that it can be used to identify priority areas for intervention. From the mapping results, it was obtained that one district/city in North Sumatra, namely Medan City, entered the red zone, then Deli Serdang Regency was included in the orange zone, then Simalungun Regency, Binjai City, Langkat Regency, Mandailing Natal Regency, Serdang Bedagai Regency and Asahan Regency entered the yellow zone. Finally, there are 25 regencies/municipalities in the green zone consisting of Kab. West Nias, Kota Tebing Tinggi, Kab. Dairi, Kab. Pakpak Bharat, Kab. Padang Lawas Utara, Kota Tanjung Balai, Kab. Labuhan Batu Selatan, Kab. Karo, Kota Padangsidimpuan, Kab. Padang Lawas, Pematang Siantar City, Gunung Sitoli City, Sibolga City, South Nias Regency, Coal Regency, Samosir Regency, Humbang Hasundutan Regency, North Tapanuli Regency, Nias Regency, Central Tapanuli Regency, North Nias Regency, Labuhan Batu Regency, North Labuhan Batu Regency, South Tapanuli Regency, and Toba Samosir Regency.